Optical soliton solution of the perturbed Fokas-Lenells equation having the cubic-quintic-septic law of self-phase modulation in the presence of chromatic and spatiotemporal dispersions - Ucar, Mehmet Fatih; Ozisik, Muslum; Secer, Aydin; Bayram, Mustafa (SPRINGER HEIDELBERG, 2024)
This study presents the optical soliton solutions of the Fokas-Lenells equation, which is a significant model for nonlinear optics. The new Kudryashov method is used to obtain the optical solutions in the form of the Fokas-Lenells equation, including the perturbation term and cubic-quintic-septic law nonlinearities. By implementing the method effectively, bright and singular soliton solutions are gained, and graphical presentations were created to analyze the effects of problem parameters on the bright soliton form. The investigated problem parameters include septic law nonlinearity, group velocity dispersion, and spatiotemporal dispersion terms.
Keywords: Physics